"The new convivencia". Issue 3 (2nd September 2019) - Fancy, Hussein
ABSTRACT: This essay offers an introduction to the recent and impassioned debates between two Spanish Arabists, Emilio González Ferrín and Alejandro García Sanjuán, about the Islamic conquest of the Iberian Peninsula in 711. While offering an overview of the controversy between them and representing their respective positions, it also calls attention to the methodological and philosophical underpinnings of the debate, underpinnings that echo earlier, trenchant disputes about medieval Spain.